Control of fresh fuel-fresh air mixing in a toroidal engine combustion chamber - Quiros, Edwin N.
The compression ignition (CI) engine is a pre-eminent in applications where fuel economy is th most important factor. The CI engine has excellent fuel economy because it operates at higher compression ratios and can burn overall lean mixtures. Burning lean mixtures is made possible by heterogeneous combustion due to fuel introduction into the cylinder late in the compression process. However, the short available time for introducing, disturbing, mixing (with air) and burning fuel causes problems. In addition, fuel is typically introduced into partially vitiated air after combustion has started. Numerous combinations of fuel injection pressure, number and size and direction of fuel injector holes, and gas motion prior to and during combustion caused both by the intake process and the combustion chamber configuration have been used to provide the required mixing in the short time available. Inevitably this results in compromises in factors such as injector and combustion chamber complexity, heat loss, volumetric efficiency, and fuel consumption.